2022
DOI: 10.1186/s12864-022-08605-6
|View full text |Cite
|
Sign up to set email alerts
|

Global leaf and root transcriptome in response to cadmium reveals tolerance mechanisms in Arundo donax L

Abstract: The expected increase of sustainable energy demand has shifted the attention towards bioenergy crops. Due to their know tolerance against abiotic stress and relatively low nutritional requirements, they have been proposed as election crops to be cultivated in marginal lands without disturbing the part of lands employed for agricultural purposes. Arundo donax L. is a promising bioenergy crop whose behaviour under water and salt stress has been recently studied at transcriptomic levels. As the anthropogenic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 91 publications
2
7
0
Order By: Relevance
“…Our results were strengthened by the evidence of the different canopy expansions observed at each site and the morphological architecture of the leaves of the studied cultivars [23,57]. It was observed that a vine with a smaller canopy would use less water than one with a larger canopy, affecting grapevine water use [58][59][60]. Cabernet Sauvignon generally showed a higher compact canopy throughout Molise, Campania, and Sicily (in this site, the training system also contributed to reducing the canopy expansion) and smallest leaves (mainly for laterals) together with the surface that, at maturity, is highly sclerotic compared to the Aglianico leaves.…”
Section: Discussionsupporting
confidence: 57%
“…Our results were strengthened by the evidence of the different canopy expansions observed at each site and the morphological architecture of the leaves of the studied cultivars [23,57]. It was observed that a vine with a smaller canopy would use less water than one with a larger canopy, affecting grapevine water use [58][59][60]. Cabernet Sauvignon generally showed a higher compact canopy throughout Molise, Campania, and Sicily (in this site, the training system also contributed to reducing the canopy expansion) and smallest leaves (mainly for laterals) together with the surface that, at maturity, is highly sclerotic compared to the Aglianico leaves.…”
Section: Discussionsupporting
confidence: 57%
“…The enzymatic antioxidant defense response differs between plant species, stage of development, organ, and duration of exposure, as well as between various stress conditions and their frequencies [67,15]. In the present study, the leaf/root GpOx activity ratio was >1 in control and [73,74,75]. According to Barceló et al (2004) [68], lignification may negatively affect root elongation by reducing cell wall extensibility, which minimizes nutrient uptake and plant growth.…”
Section: Guaïcol-peroxidase Activity (Gpox)mentioning
confidence: 44%
“…As reported by Lux et al (2011), the physical barriers like Casparian strip and lignification can limit Cd translocation to the shoots. Santoro et al (2022) believed that the up-regulated gene involved in cell wall remodeling and lignification had the function of avoiding cadmium uptake. It's probably another way for Tartary buckwheat to respond to Cd stress (El Rasafi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The cell wall is the first barrier for Cd to get into the cell and the major site to immobilize Cd by ion binding, which is an important strategy to detoxify Cd in plants ( Shanmugaraj et al., 2019 ; Santoro et al., 2022 ). The GMGT1 gene (Gene ID: FtPinG0100416000.01 ) is involved in galactomannan biosynthesis ( Edwards et al., 2004 ).…”
Section: Discussionmentioning
confidence: 99%